YIIFSWA II OPENDAY - Interview with Edwin Y. Sakyi - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Interview with Edwin Y. Sakyi, MOFA Ghana at YIIFSWA II Open Day at IITA Ibadan, Nigeria. YIIFSWA-II showcases High Ratio Propagation Technologies and demonstrates large scale production of early generation seed yam